2020
DOI: 10.21203/rs.3.rs-32214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Involvement of Final year Medical Students in Hospital work during COVID-19 pandemic: A students’ perspective

Abstract: Background: The Coronavirus disease (COVID-19) has upended medical education. This pandemic has risen uncertainty over the start of the normal routine of studies in medical universities. Amidst the worldwide shortage of doctors, there is widespread dilemma and disagreement regarding the role of the medical students during this pandemic. Medical education is suspended and the students are barred from being direct medical providers unless there is a critical need for the additional healthcare workforce. Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The students felt that the basic skills to work in the hospital were acquired by only 32.3% the ndings are similar to previous studies carried on medical students 7 . 42.3% of interns feel that they have acquired the required skills to be working in hospitals, only 17.5% of the third-year students feel that they have acquired skills to be working in the hospital.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The students felt that the basic skills to work in the hospital were acquired by only 32.3% the ndings are similar to previous studies carried on medical students 7 . 42.3% of interns feel that they have acquired the required skills to be working in hospitals, only 17.5% of the third-year students feel that they have acquired skills to be working in the hospital.…”
Section: Discussionsupporting
confidence: 86%
“…This study reveals that 52.9% of dental students are highly motivated to work as health care professionals. Another study reported motivation by medical students to be 62.2% during the COVID-19 pandemic 7 . Other ndings indicate that the morale of the health professional workers was low in the beginning but was gradually built receiving motivational and psychological support from the general public and o cials 8 .…”
Section: Discussionmentioning
confidence: 99%